Kurikulum Dalam Perspektif Filsafat Pendidikan Islam - Nur Indah Sari; Fitriyah (Program Studi Pendidikan Agama Islam, 2024)
The Islamic education philosophy perspective curriculum is based on a solid foundation, namely the Al-Qur'an and Hadith. This foundation guides every individual in carrying out their duties and functions as caliph and gaining eternal life in this world and the afterlife based on Islamic education. Philosophy plays an important role in achieving the general goals of education and directs that the curriculum designed contains Islamic values, and is in line with universally accepted truths. The purpose of this writing is to find out about the Islamic education curriculum, and the curriculum from the perspective of Islamic education philosophy. The results of writing this article show that through philosophy it can be determined how to determine the benchmarks for the success of the educational process, by referring to curriculum principles, including: Philosophical Principles, Sociological Principles, Organizational Principles, Psychological Principles. The Islamic education curriculum has its own characteristics which are based on principles and teaching materials based on the Koran and Hadith.